ANALISIS PENGARUH FAKTOR EKONOMI PADA SAHAM PERBANKAN DI BURSA EFEK INDONESIA - Sumarsih Sumarsih (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2019)
This study aims to determine the effect of economic factors on banking stocks on the Indonesian stock exchange. The sampling technique used was purposive sampling. Analysis of the data used is the method of multiple regression analysis using SPSS 20. The empirical results of this study indicate that microeconomic factors namely Capital Adequacy Ratio, Non Performing Loans have a negative but not significant effect on stock returns while Operational Costs on Operational Income have a negative and significant effect on return stock. The macroeconomic factors namely inflation shows a negative and significant influence on stock returns. The implication is that this research can strengthen signal theory and arbitrage pricing theory and add insight to future researchers, as well as additional references for banking companies in considering the role of predictor variables as in this study. which affects stock returns.